Plurispore development of Cladosiphon okamuranus Tokida (Chordariaceae, Phaeophyta) - Zhu, Qinghua; Zhang, Xuecheng; Xu, Di; Arunakumara, KKIU; Shi, Yanxia; Zhu, Luying (Bangladesh Journal of Botany, 2008)
<!–[if gte mso 9]> sebahattin 11.6568 <![endif]–><!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if !mso]> <![endif]–> <!–[if gte mso 10]> <![endif]–> Development of plurispores and effects of temperature on their attachment to substrata were studied using mature plurilocular sporangia of Cladosiphon okamuranus Tokida. Development of plurispore showed the disc type, a large number of assimilatory filaments were found to develop from the middle or central part of a disc. These compact and parallel assimilatory filaments formed pseudoparenchyma (multiaxial) with abundant lateral branches. The attachment and development of a plurispore were affected significantly by temperature. Suitable seeding temperature was found to be 17-26Âº and 26Â° being optimum for successful attachment. At a temperature over 26ÂºC, the plurispore could not attach tightly to a substratum or developed poorly. Â Â Key words: Plurispores, Cladosiphon okamuranus, Multiaxial, Hair, Pseudoparenchyma DOI = 10.3329/bjb.v36i2.1505 Â Bangladesh J. Bot. 36(2): 157-162, 2007 (December)